2018
DOI: 10.1037/vio0000136
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to increasing women’s empowerment status and reducing domestic violence: Results of a cluster-randomized controlled trial in a West African country.

Abstract: Objective: This is the first experimental study testing the effects of an economic intervention alone and in combination with a family focused component, on women's empowerment status and family violence in Burkina Faso. Method: The 3-arm cluster randomized controlled trial with baseline and 1-year follow-up included 360 ultrapoor married women from 12 villages. Villages were randomized to the 3 study arms: economic intervention for women (Trickle Up/TU), a combination of economic intervention and family coach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
0
25
0
1
Order By: Relevance
“…Five SHG and VSLA studies used an experimental design. This included Bass et al (2016), Beaman et al (2014), Desai and Joshic (2013), Ismayilova et al (2018), Karlan et al (2017) and Kumar et al (2018). All six studies had some concerns related to risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Five SHG and VSLA studies used an experimental design. This included Bass et al (2016), Beaman et al (2014), Desai and Joshic (2013), Ismayilova et al (2018), Karlan et al (2017) and Kumar et al (2018). All six studies had some concerns related to risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…We failed to find evidence of improvements in women’s agency at the relationship/family level around decision making or uses of the loans provided through the program. Although the evidence remains mixed, some studies have shown that strengthening women’s agency can lead to a reduction in IPV by improving their involvement in decision making (Hadi, 2005; Iyengar & Ferrari, 2011) and enhancing their financial autonomy (Ismayilova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the connection between women’s economic empowerment and risk of IPV is mixed, though it has focused thus far on physical, emotional, and/or sexual forms of IPV and not economic coercion (Ismayilova et al, 2018; Naved et al, 2018; Schuler & Nazneen, 2018). Yount, Cheong, Khan, et al (2021) found no evidence that women’s participation in microfinance programs increased their risk of IPV, including economic coercion.…”
Section: Theoretical Frameworkmentioning
confidence: 99%